Understanding the sensitivity of numerical slope stability analyses to geotechnical and other input parameters - Wines, D.R. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Most geotechnical inputs required to perform a slope stability analysis involve some degree of uncertainty (i.e. the exact value or variability for these inputs is not known). Sensitivity analyses are often performed to assess the influence of parameter variability on the predicted slope behaviour. It is therefore valuable to understand which inputs are most important for a slope stability analysis, and where efforts should be focused with respect to field and laboratory investigations and sensitivity analyses. Three-dimensional numerical slope stability analyses have been performed to assess the influence of several inputs on the predicted slope behaviour. Analyses have been run for different slope failure mechanisms, including rotational, wedge and toppling failures. Inputs that have been assessed include the rock mass properties, the discontinuity properties, the in situ stresses and the pore pressures. The analyses indicate that all of the inputs have some influence on the predicted slope behaviour. However, the adopted rock density, strength parameters (for the rock mass and discontinuities) and pore pressures have the most significant influence on the predicted Factors of Safety. This indicates that investigation of the rock density, strength properties and pore pressures should be prioritised when performing slope stability analyses. In a hard rock environment, development of a reliable structural model is also critical.